The impact of professional learning communities on pre-service teachers’ professional commitment - Cheng, Chunsong; Zhao, Jinzhen (Frontiers in Psychology, 2023)
While in-service teachers’ professional commitment has gained significant attention in recent years, researches on pre-service teachers’ professional commitment is still insufficient, particularly with regard to the effect that professional learning communities play on pre-service teachers’ professional commitment. In this context, this study employed a mixed-methods design to investigate the impact of workshops for teaching competitions as a professional learning community on pre-service teachers’ professional commitment in China. A questionnaire survey was administered to pre-service teachers who had workshop experiences (n=43) and their classmates who did not have workshop experiences (n=98) in to examine the effect of workshops for teaching competitions as a professional learning community on pre-service teachers’ professional commitment. Follow-up qualitative interviews with 5 pre-service teachers with workshop experiences were conducted to explain the reasons behind such effects. The results showed that workshop experiences had significant and positive effects on pre-service teachers’ professional commitment and the characteristics of shared vision, collaboration, and reflective dialogue affected their professional commitment from three perspectives: commitment to teaching as a career, personal time investment, and interest in professional development.